Prenatal diagnosis, ultrasound findings and pregnancy outcome of 7q11.23 deletion and duplication syndromes: what are the fetal features? - Xiaojin Luo; Hongyan Niu; Fei Zhou; Xiaohang Chen; Yuanyuan Pei; Weiqiang Liu; Fengxiang Wei (BMC, 2024)
Abstract Objective Analyze the ultrasound findings, single nucleotide polymorphism array (SNP-array) results, and pregnancy outcomes of fetuses with 7q11.23 deletions and duplications in the second and third trimesters. Investigate the prenatal ultrasound characteristics and follow up information of these fetuses. Methods Seven fetuses were diagnosed with 7q11.23 deletion and six with 7q11.23 duplication via SNP-array at the prenatal diagnosis center of a single Chinese tertiary medical center from January 2017 to May 2024. Maternal demographics, ultrasound findings, SNP-array results, pregnancy outcomes, and follow-up information were comprehensively reviewed and analyzed. Results The copy number variations (CNVs) ranged from 1.43 Mb to 1.78 Mb in cases of 7q11.23 deletions and from 1.42 Mb to 1.68 Mb in cases of 7q11.23 duplications. These CNVs encompassed 29 OMIM-listed genes, including ELN, DNAJC30, GTF2IRD1, and GTF2I. Among the seven cases of 7q11.23 deletion syndrome, six exhibited ultrasound abnormalities. The main clinical phenotypes included three cases of intrauterine growth restriction and four cases of cardiovascular system abnormalities, specifically two cases with ventricular septal defects, one case with aortic narrowing, and one case with supravalvular pulmonary stenosis. One case was particularly notable, exhibiting complex multi-organ structural malformations. Out of six cases of 7q11.23 duplication syndrome, five exhibited ultrasound abnormalities. These included two cases of cardiovascular abnormalities: one case with a widened left ventricle and another case with a shortened fetal humerus length. One case revealed complex multi-organ structural malformations, including hydronephrosis, a microgallbladder, and a cleft lip and palate. All seven cases of 7q11.23 deletions and three cases of 7q11.23 duplications opted for termination of the pregnancy. The remaining three cases of 7q11.23 duplications chose to continue the pregnancy. One case underwent surgical treatment for a ventricular septal defect after birth, and the prognosis was favorable. Another case involved a full-term delivery, this child was followed up at the age of 4 and exhibited a phenotype of poor language expression ability. Conclusion Our study broadened the clinical phenotype spectrum of fetuses with 7q11.23 deletions and duplications. Additionally, it conducted a preliminary evaluation of prenatal ultrasound findings and postnatal clinical phenotypes in follow-up cases. The clinical phenotype of fetuses with 7q11.23 deletion and duplication syndromes involves multiple systems and is relatively complex. Cardiovascular abnormalities and intrauterine growth restriction are the most common clinical manifestations observed in prenatal 7q11.23 deletion syndrome. Fetuses with 7q11.23 duplications exhibit a wide range of clinical phenotypes that lack specificity.